ENVIRONMENTAL POLITICS: THE IMPACT OF THE ESTABLISHMENT OF A PALM OIL FACTORY IN DENSELY POPULATED AREA (CASE STUDY OF PULO PADANG VILLAGE, LABUHANBATU REGENCY) - Sonya Amelia; M.Akmal; Muntasir; Muhammad Bin Abu Bakar; Teuku Muzaffarsyah (RADJA PUBLIKA, 2025)
This study examines the development of a palm oil mill in a densely populated area such as Pulo Padang Village, which has created complex dynamics related to environmental politics and social conflict. This study aims to evaluate the impact of development on society and the environment, as well as the resolution process. A qualitative approach method was used with interview, observation, and documentation techniques for residents, the government, and the company. The results show that the conflict is rooted in a lack of transparency, minimal community participation, and ecological impacts that are detrimental to the surrounding community. The government needs to strengthen regulations and actively involve the community to achieve equitable sustainable development. These findings emphasize the importance of an inclusive approach, constructive negotiation, and the application of environmental justice principles to reduce conflict and improve socio-ecological sustainability.